Investigating the effect of different water and soil conservation practices on some soil properties - Javad Khalaji; Nasrin Gharahi; Mehdi Pajouhesh (محیط زیست و مهندسی آب, 2021)
Studying the effects of different types of water and soil protection systems on soil properties is of great importance in soil planning and management and is considered as a move towards sustainable development. The purpose of this study was to investigate the effect of three systems of water and soil protection in Chaharmahal and Bakhtiari province on topsoil and subssoil of soil organic carbon content, bulk density, soil stability, nitrogen, potassium, phosphorus, soil texture, acidity, electrical conductivity and soil permeability at depth of 0-30 and 30-60 cm. By comparing each of the soil physical and chemical properties in exclosure, contour furrow and Pitt seeding and the control areas, it was concluded that in soil and water conservation systems, organic carbon, bulk density, stability, Phosphorus, soil texture, acidity, electrical conductivity of topsoil did not increase significantly and in some cases nitrogen and potassium increased significantly (at the level of 5%). The lowest amount of surface soil nitrogen (0.087%) was observed in excavation improvement operation which had a significant difference with surface soil nitrogen (0.072%) in contour operation. The lowest and highest amount of surface soil organic carbon with significant differences (1.02 and 1.43%) were related to pitt seeding and contour farrow, respectively. Comparison of permeability data in control and protected areas showed that the implementation of water and soil protection operations had a positive effect on soil permeability. In general, the effect of water and soil protection systems on improving soil quality is not absolute and depends entirely on different climatic conditions, geology of each region.